Potential Analysis of New Hospital Locations in Tasikmalaya City Using Geographic Information Systems - Efri Triana Nur Arifin (Universitas Veteran Bangun Nusantara, 2022)
Tasikmalaya is one of the cities in West Java Province with a total population of 716,155 people in 2020 with a growth rate of 12.70% compared to the population in 2010. Cihideung District is the area with the largest population density of 13,202 people/km2 and Tamansari District is the area with the smallest population density of 2,083 people/km2. Meanwhile, the population density of Tasikmalaya City is around 3,887 people/km2. However, the number of existing hospitals has not increased significantly and is also unable to accommodate and reach this very large population. For this reason, it is necessary to add hospitals with strategic locations, one way to do that can be done with the help of a geographic information system. By using the descriptive-quantitative method, the existing data were analyzed using a correlation approach and depicted factually, systematically and accurately. Referring to the data from the overlay analysis, the determination of the new hospital land location should be placed in areas with high population density, these locations include the districts of Cibereum, Mangkubumi, Bungursari, and Purbaratu, as well as in the northern and southern areas of Tasikmalaya City.